2021
DOI: 10.1016/j.hroo.2021.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Advanced management of ventricular arrhythmias in chronic Chagas cardiomyopathy

Abstract: High-density mapping during sinus rhythm can identify late isochronal regions that are then targeted for ablation. Preablation cardiac magnetic resonance imaging with late enhancement can identify potentials areas of arrhythmogenesis. Therapeutic alternatives for VT management include antiarrhythmic drugs and modulation of the cardiac autonomic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Only two drugs are available as a therapeutic option for Chagas disease (nifurtimox and benznidazole) and their effectiveness is far from ideal ( Pérez-Molina et al, 2021 ). While in the acute Chagas disease the treatment can achieve cure in up to 76% of patients ( Cançado, 2002 ), the efficacy in the chronic phase is uncertain ( Santacruz et al, 2021 ) and is not correlated with a better outcome ( Cevey et al, 2017 ; Morillo et al, 2015 ). Cevey et al, for example, showed that treatment with benznidazole for 15 consecutive days during the chronic phase did not improve the left ventricular function in mice ( Cevey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only two drugs are available as a therapeutic option for Chagas disease (nifurtimox and benznidazole) and their effectiveness is far from ideal ( Pérez-Molina et al, 2021 ). While in the acute Chagas disease the treatment can achieve cure in up to 76% of patients ( Cançado, 2002 ), the efficacy in the chronic phase is uncertain ( Santacruz et al, 2021 ) and is not correlated with a better outcome ( Cevey et al, 2017 ; Morillo et al, 2015 ). Cevey et al, for example, showed that treatment with benznidazole for 15 consecutive days during the chronic phase did not improve the left ventricular function in mice ( Cevey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%